Profile of Wushu Sports Development in Gianyar City - Manna Durrunnafisa (Universitas Sebelas Maret, 2022)
This study aims to determine and describe the state of the organization, human resources in the organization, achievement development, facilities and infrastructure, training programs and achievements, as well as funding for the wushu sport in the city of Gianyar Bali from 2015 to 2020. This study uses a qualitative descriptive method. The subjects in this study were the vice chairman, coach, and senior Wushu athlete of Gianyar City, Bali. Data were collected by observation, interviews, and documentation. The results showed that the state of the Wushu organization in the City of Gianyar Bali was running well and had clear goals, the administrators, coaches and athletes carried out their duties according to their fields, the coaching that had been carried out had gone through the stages of problem solving, breeding and athletes' achievements, the facilities and infrastructure were quite good and adequate, well-organized exercise program. Based on the results of research and discussion of achievement coaching, there are still things that must be developed so that achievement can increase further. The role of the coach to improve the training program should be given more attention for the progress of the athlete and presented more variedly. The management of sports organizations should be more adapted between the fields. Sources of funds that are managed should be done openly to athletes so that no one thinks negatively about funding.